2018
DOI: 10.24198/jnc.v1i3.18983
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Quality of Life of Nurses who Work in the Intensive Care Unit and Emergency Unit

Abstract: Nurses need compassion when providing health services. Compassion felt by nurses can be Compassion Satisfaction (positive aspects) and Compassion Fatigue (negative aspects), and may affect nursing care and Nurses’ Professional Quality of Life. The tendency to negative aspects will be felt by the nurses themselves, patients and hospitals. The purpose of this study was to determine the quality of life of professionals (Professional Quality of Life) nurses in the Intensive Care Unit (ICU) and Emergency Room (ER) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Overall, the total result of ProQOL in this study was moderate level among ICU nurses which is consistent with many studies (Adolfo, 2021;Alshehry et al, 2019;Remegio et al, 2021;Kim et al, 2015;Wulandari et al, 2018). In fact, the workload in ICUs (Mohammadi et al, 2017), dealing with a critical patient Mohammadi et al (2017), or difficulty to sleep Alshehry et al (2019), can make nurses to not fell high level of ProQOL in ICUs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, the total result of ProQOL in this study was moderate level among ICU nurses which is consistent with many studies (Adolfo, 2021;Alshehry et al, 2019;Remegio et al, 2021;Kim et al, 2015;Wulandari et al, 2018). In fact, the workload in ICUs (Mohammadi et al, 2017), dealing with a critical patient Mohammadi et al (2017), or difficulty to sleep Alshehry et al (2019), can make nurses to not fell high level of ProQOL in ICUs.…”
Section: Discussionsupporting
confidence: 87%
“…ProQOL is concerned with the level of satisfaction experienced by nurses as a result of their employment (Wulandari et al, 2018). ProQOL includes two dimensions: compassion satisfaction and compassion weariness.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the number of patients is the biggest barrier perceived by nurses is the safe handling of equipment or surfaces that can be potentially contaminated in the patient's environment. This barrier arises from environmental aspects and other aspects Wulandari, A. E., Susilaningsih, F. S., & Somantri, I. (2018).…”
Section: The Biggest Barrier Perceived By Nurses On Handling Environmmentioning
confidence: 99%
“…Additionally, research on Croatian critical care nurses showed a high level of emotional Corresponding author: Leona Cilar, University of Maribor,Faculty of Health Sciences,Nursing Department,Žitna ulica 15,Maribor,Slovenia;email: leona.cilar1@um.si exhaustion and depersonalization (Friganović & Selič, 2020). Quality nursing care gives nurses a feeling of satisfaction with their job, which is often closely related to professional quality of life (Wulandari et al, 2018). "Professional quality of life is the quality one feels in relation to their work as a helper.…”
Section: Introductionmentioning
confidence: 99%